The political economy of public-private good of open, distance, higher education institutions in South Africa - Ntshoe, Isaac (University of the Free State, 2011)
The thrust of this article is on the issues of who pays, who should pay and who benefits from open distance higher education in the current context of global competition, on the one hand, and the widening of participation, social equity and redress, on the other, in South Africa. The discussions emphasise the public-private good dichotomy, as well as social and private returns and how open and distance higher education promotes social equity and efficiency. The article explores the extent to which open distance higher education promotes the widening access for previously disadvantaged groups and improvement of social and economic equities.

Die kern van hierdie artikel is die kwessie van wie betaal, wie moet betaal en wie voordeel trek uit toeganklike afstandsonderrig in die huidige konteks van globale kompetisie aan die een kant, en die verbreding van samewerking, sosiale ekwiteite en regstelling in Suid-Afrika aan die ander kant. Die basis van bespreking is die openbare-private bate-tweedeling, asook die sosiale en private omset en die vraag hoe toeganklike en afstandsonderrig in hoër onderwys sosiale ekwiteit en effektiwiteit bevorder. Die artikel ondersoek die mate waarin afstandsonderwys meer toeganklik vir agtergeblewe studente gemaak kan word en die verbetering van sosiale en ekonomiese ekwiteite.
Keywords: Open distance education; Public-private good dichotomy; Social equity and efficiency; Higher education in South Africa